PENERAPAN TEKNOLOGI TEPAT GUNA UNTUK PENINGKATAN PRODUKTIFITAS USAHA PEMBUATAN PEYEK DI SUNGAILIAT KABUPATEN BANGKA - Muhammad Yunus; Idiar Idiar; Erwansyah Erwansyah (Jurnal Pengabdian Masyarakat Polmanbabel, 2022)
This Community Service activity in the business of making peanut crackers in MSME "SURTAM" aims to improve one of the existing production stages, namely the manufacture of coconut milk. The process of making coconut milk carried out by partners is still traditional which causes the energy used to be quite large and takes a long time. This causes the production of peanut brittle has not been maximized. The method used to solve production problems is to design and manufacture a coconut milk squeezer machine. After that, partners are given training on how to use and maintain the machine in order to carry out maximum production. The benefit of this activity is the synergy between universities and local industries related to the application of appropriate technology that can be used directly by MSME actors in their production activities. There is an increase in the production capacity of partners, especially at the stage of making coconut milk, where before community service activities, the time needed by partners to squeeze the grated 6 coconuts for approximately 1 hour, and after the activity becomes approximately 15 minutes. In addition, partners already have the knowledge and skills in operating and caring for coconut milk extortion machines used in the peanut butter production process.